2022
DOI: 10.3390/socsci11050196
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Adolescents, Parents, Service Providers, and Teachers on Mobile Phone Use for Sexual Reproductive Health Education

Abstract: Mobile health (mHealth) programs offer opportunities to improve the sexual and reproductive health (SRH) of adolescents by providing information. This paper reports the findings of a study carried out in Homabay County, Kenya, to assess stakeholders’ perspectives on access to and use of mobile phones by adolescents for SRH education. We aimed to establish whether mobile phones could facilitate access to SRH information by adolescents and the barriers to be addressed. This was a qualitative exploratory study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This indicates the need to engage families, particularly parents, as active agents in adolescent CSE programs. One such study, the Family Matter Project in Tanzania worked with caretakers of adolescents to promote SRH communication [ 35 ]. The intervention utilized the information–motivation–behavioral (IBM) model to provide targeted content [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the need to engage families, particularly parents, as active agents in adolescent CSE programs. One such study, the Family Matter Project in Tanzania worked with caretakers of adolescents to promote SRH communication [ 35 ]. The intervention utilized the information–motivation–behavioral (IBM) model to provide targeted content [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…One such study, the Family Matter Project in Tanzania worked with caretakers of adolescents to promote SRH communication [ 35 ]. The intervention utilized the information–motivation–behavioral (IBM) model to provide targeted content [ 35 ]. The study demonstrated significant improvements in communication between caretakers and adolescents which could indicate the intervention’s capacity to break down cultural barriers that previously limited sexuality discussions [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review qualitatively explored the experiences and perceptions of young peoples’ use of mobile phone platforms for SRH information and services in rural settings in LMICs using the GRADE-CERQual approach. Evidence has shown that mHealth technology platforms have the potential to address numerous SRH information and services access barriers for young people in rural contexts in LMICs (16, 18, 56-59). The study findings reported preferences and barriers for use of mHealth-based platforms for SRH information and services among rural young people across rural LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Whiles mobile phone-based platforms are becoming increasingly popular among young people for SRH services in rural contexts in LMICs, platforms such as WhatsApp, Facebook and Twitter are less used and preferred by young people (42, 51, 52). Few young people had used these platforms due to the requirement for smart phones and their associated high cost and lack of technological skills (16, 86, 87). Some participants also felt that these platforms were not familiar among them in their settings and hence their low usage.…”
Section: Discussionmentioning
confidence: 99%
“…Personal cost of providing health delivery services in rural settings in LMICs constitutes a disproportionate share of cost for HCPs and poor young people with low incomes [39]. HCPs said that subsidizing the cost of mobile phones and call credit for rural health workers and the creation of a hotline dedicated to mHealth SRH services [65] in rural areas of LMICs is critical for delivery of SRH information and services among rural and remote populations [66][67][68].…”
Section: Discussionmentioning
confidence: 99%